2018
DOI: 10.1016/j.ijwd.2018.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Medical dermatologic conditions in transgender women

Abstract: Many previous reviews and studies on transgender dermatology have highlighted the expected dermatologic manifestations of hormone affirmation therapy in transgender patients. Others have highlighted attitudes and practices of both transgender patients and medical professionals taking care of these patients. This review compiles data from other, lesser known aspects of transgender dermatology, including neovaginal concerns, neoplastic concerns (both neovaginal and cutaneous), autoimmune conditions, and the sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 46 publications
0
3
0
1
Order By: Relevance
“…Karzinome in der Neovagina oder der Vulva sind selten, sie treten dann sporadisch vor allem bei Hinzukommen von Risikofaktoren auf. Nach peniler Inversionstechnik ist hier in erster Linie das HPV(humane Papillomviren)-assoziierte Plattenepithelkarzinom zu nennen [24]. Die Vorsorge erfolgt durch die regelmäßigen vaginalen Einstellungen.…”
Section: Komplikationenunclassified
“…Karzinome in der Neovagina oder der Vulva sind selten, sie treten dann sporadisch vor allem bei Hinzukommen von Risikofaktoren auf. Nach peniler Inversionstechnik ist hier in erster Linie das HPV(humane Papillomviren)-assoziierte Plattenepithelkarzinom zu nennen [24]. Die Vorsorge erfolgt durch die regelmäßigen vaginalen Einstellungen.…”
Section: Komplikationenunclassified
“…In both studies, it was found that their vaginal microbiome was more similar to the skin and gut microbiome, possibly due to skin grafts during neovaginal surgery. There is high therapeutic potential in understanding how the vaginal microbiome contributes to symptoms following neovaginal surgery, but it is a multifaceted problem with many important considerations reviewed extensively in Mundluru & Larson, 2018 61 .…”
Section: Gender Affirming Treatmentmentioning
confidence: 99%
“…3 A growing body of literature is emerging to define these effects and their management, which commonly include acne, changes in hair distribution or density, and hyperpigmentation. 3,4 An increased susceptibility to female predominant autoimmune conditions has also been suggested, 5 raising concern that transgender females on long-term HT may additionally be at risk for other conditions commonly linked to estrogen exposure, such as porphyria cutanea tarda (PCT), erythema nodosum, vascular lesions, and cutaneous manifestations of changes in bile or lipid metabolism. 6 We report the case of a 55-year-old woman (maleto-female transgender) who presented with PCT following a change in HT that led to supratherapeutic estrogen.…”
Section: Introductionmentioning
confidence: 99%